House price determinants and their impact on consumption and fertility - Wong, Wang Li (2017)
The role of housing market in an economy is important in modern era as it brings a huge impact to an economy. Substantial increase in house values over recent years (2000 - 2013) have led to an economic policy debate on its effects on economy. This study investigated the house price determinants and its effects on consumption and fertility using time series and panel data in Malaysia. There is a mounting amount of literature that reveals the significance of fundamentals variable on housing price and its strong relationship between housing wealth and consumption, as well as housing price on fertility. Income and population is the major fundamental variables to determine housing price. But the increasing housing price may cause by speculation force and foreign inflow, which are prone risk in an economy. This study consistently found that the housing price hike from year 2000 to 2013 were supported by fundamentals, whereas speculation force was weak or yet to exist. On the top of that, the impact of foreign inflow on housing price was found to be limited. Housing price impacts household in several channels. Housing wealth channel traditionally impact household spending through financial system. Malaysia has unique financial system which is different from most of the countries, therefore the impact of housing wealth remained ambiguous. This study also found that the price variation in the Malaysia housing market is associated with consumer spending but in a different manner when compared with most of the existing literature. The absent of various housing related securities in Malaysia is one of the possible reason that caused the distinction of consumer spending behaviour on housing price variation. Fertility decision is generally determined by socioeconomic factors. Income, healthcare cost, education cost and other cost of living were the main determinants of fertility. The increasing housing price in Malaysia may impact fertility in both positive and negative way by wealth and cost of living channel. This study found that fertility is associated with increasing housing price and it functions as a cost of living and found negatively associated with fertility.